WANITA KARIR DALAM TINJAUAN MAQASHID AL-SHARI’AH - Muhammad Ichsan; Erna Dewi (Institut Agama Islam Negeri Batusangkar, 2020)
Today's society considers that women's duty is not only helping her husband take care of the household, but also studying as high as possible to have career in order to channel their abilities and education.The current needs of life are increasingly forcing them to work and leave home to help their husbands meet their daily needs for themselves and their families. Women are allowed to be outside the house provided that they can protect themselves from evil, adultery and harm to themselves.A married woman may be outside the house on condition that she gets permission from her husband, covers her genitals, and does not use colognes, jewelry or anything excessive that can attract the attention of other men or even provoke lust and cause defamation. Meanwhile, single one must get permission from her parentsin order to maintain her honor and theirs, because the goal is onlyto run the Islamic sharia properly and get His pleasure.